A20 expression in dendritic cells protects mice from LPS‐induced mortality. Issue 3 (28th December 2014) - Xuan, Nguyen Thi; Wang, Xu; Nishanth, Gopala; Waisman, Ari; Borucki, Katrin; Isermann, Berend; Naumann, Michael; Deckert, Martina; Schlüter, Dirk
<x xml:space="preserve">Abstract</x> DCs contribute to immune homeostasis under physiological conditions and regulate the immune activation during infection. The deubiquitinase A20 inhibits the activation of NF‐κB‐dependent immune reactions, and prevents the hyperactivation of DCs under steady‐state conditions. However, the role of DC‐specific A20 under pathological conditions is unknown. Here, we demonstrate that upon injection of low‐dose LPS, mice with DC‐specific A20 deletion (CD11c‐Cre A20fl/fl) died within 6 h, whereas A20fl/fl controls survived. LPS‐induced mortality in CD11c‐Cre A20fl/fl mice was characterized by increased serum levels of IL‐2, IL‐10, IL‐12, IFN‐γ, and TNF. Upon LPS stimulation, the activation of NF‐κB and ERK‐NFATc3 pathways were enhanced in A20‐deficient DCs, resulting in an increased production of IL‐2, IL‐12, and TNF both in vitro and in vivo. Targeted inhibition of ERK in A20‐deficient DCs abolished the increased production of IL‐2. A20‐deficient DCs failed to induce LPS tolerance, which was independent of T cells and the intestinal flora, since T‐cell depletion and decolonization of CD11c‐Cre A20fl/fl mice could not prevent death of LPS‐challenged CD11c‐Cre A20fl/fl mice. In conclusion, these findings show that DC‐specific A20 preserves immune homeostasis in steady‐state conditions and is also required for LPS tolerance.